2007
DOI: 10.1615/critrevtherdrugcarriersyst.v24.i4.10
|View full text |Cite
|
Sign up to set email alerts
|

Spray-Dried Powders for Pulmonary Drug Delivery

Abstract: Powders for inhalation are traditionally prepared using a destructive micronization process such as jet milling to reduce the particle size of the drug to 2-5 mum. The resultant particles are typically highly cohesive and display poor aerosolization properties, necessitating the addition of a coarse carrier particle to the micronized drug to improve powder flowability. Spray-drying technology offers an alternative, constructive particle production technique to the traditional destructive approach, which may be… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
39
0
1

Year Published

2009
2009
2016
2016

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 106 publications
(41 citation statements)
references
References 104 publications
1
39
0
1
Order By: Relevance
“…Nevertheless, the fate of microspheres entering the lungs is dependent on the manufacturing material and technique and on the delivery device. Spraydrying is a very valuable technique for producing dry powders suitable for pulmonary delivery of drugs (63). Spray-drying of compounds of different compositions resulted in a change of particle morphology (64), which is of potential importance in the development of therapeutic powder aerosol formulation.…”
Section: Chitosan Microspheresmentioning
confidence: 99%
See 1 more Smart Citation
“…Nevertheless, the fate of microspheres entering the lungs is dependent on the manufacturing material and technique and on the delivery device. Spraydrying is a very valuable technique for producing dry powders suitable for pulmonary delivery of drugs (63). Spray-drying of compounds of different compositions resulted in a change of particle morphology (64), which is of potential importance in the development of therapeutic powder aerosol formulation.…”
Section: Chitosan Microspheresmentioning
confidence: 99%
“…It has already been established that spray drying constitutes a very valuable technique for producing dry powders adequate for pulmonary delivery of drugs (63,64).…”
Section: Chitosan-based Nanoparticlesmentioning
confidence: 99%
“…Spray-drying has been utilised for the preparation of microparticles with controlled particle morphology and suitable for pulmonary drug delivery (7,8). Previous studies showed that varying the feed solvent (23) and adjusting the outlet drying temperature (24) affected particle morphology, and concomitantly manipulating feed concentration and atomisation rate might produce particles with different degrees of surface corrugation (13,14).…”
Section: Preparation Of Spray-dried Shl Particlesmentioning
confidence: 99%
“…In the literature, various novel particle engineering technologies, including spray-drying (6)(7)(8), spray freeze-drying (9), supercritical fluids (10), controlled crystallisation (11,12), etc., have been well documented for the preparation of respirable particles. Based upon the mechanisms by which the engineered particles provided the improved aerosol performance of DPI, Chow and colleagues (6) classified the engineered particles into three types, namely large porous particles, and particles with surface chemical modification and with irregular surface, respectively.…”
Section: Introductionmentioning
confidence: 99%
“…Powders produced by such high energy processes exhibit strong inter-particulate attractions, leading to agglomeration. Moreover, micronization does not permit precise control of particle morphology, size distribution, particle density or surface composition leading to variations, and produces defects and/or amorphous regions on crystal surfaces, resulting in altered aerosolization properties and posing considerable formulation challenges [20][21][22]. This has led to alternative ways of controlling particle size distribution, particle porosity, surface roughness, particle density, etc.…”
Section: Introductionmentioning
confidence: 99%